Analisis Risiko Kecelakaan Kerja pada Proyek Konstruksi Menggunakan Metode Bowtie (Studi Kasus: Pembangunan Terowongan Joyoboyo Surabaya) - Nelson Elkana Daud Way; Maulidya Octaviani B; Wisnu Abiarto N; Sekar Ayu Kuncaravita (Jurnal Aplikasi Teknik Sipil, 2025)
In the implementation of construction such as the Joyoboyo Tunnel, there are always risks that can arise in every activity or work on the project. The purpose of this study is to analyze the causes, impacts and responses to the most dominant risks and control methods to reduce the risk of work accidents in the Joyoboyo Tunnel Construction project. Data collection techniques through distributing questionnaires with data analysis techniques through Risk Identification and Assessment and Bowtie. The results of the study stated that the causal factors for the risk of "Land prone to landslides" with a risk value of 25. Then the causal factors for the risk of "Low oxygen levels" with a risk value of 20. For the causal factors for the risk of "Scaffolding has not been installed properly" and the causal factors for the risk of "Falling Material in Excavation" with a risk value of 16 with high risk category